Investigation of Nested Nemo Schemes in mobile network environment - Ali, Mohammed Babiker; Hassan Abdalla Hashim, Aisha; El-Azhary, Ismail (IEEE, 2013)
Using of mobiles and wireless devices becomes very important in recent years, due to the increase of services and applications they provide. The major issue is to provide seamless mobility to achieve better performance. The Internet Engineering Task Force has developed Mobile IP which allows Mobile node moving from a network to another using its original IP address. The Internet Engineering Task Force also developed the Mobility Basic Support Protocol (BSP) for managing a mobile network as a single unit. When a mobile router in mobile network is attached to another mobile router in another mobile network, it makes a hierarchical form known as Nested Mobile Network (NMN). NMN suffers from major problems in the case of multi-level nesting. Some issues such as signaling cost, packet losing and delay are affect directly nested network performance. This Paper investigates the current approaches dealing with Nested NEMO Schemes in mobile network environment. It highlights the advantages and the limitations of these approaches. Both the qualitative and the quantitative evolutions of these proposals are presented.